Hybrid Cryogels with Advanced Adsorbent Properties for Penicillin - Marinela-Victoria Dumitru; Teodor Sandu; Iulia Elena Neblea; Horia Iovu; Anita-Laura Chiriac; Ionut Cristian Radu; Andrei Sarbu; Tanta Verona Iordache (Chemistry Proceedings, 2022)
In recent years, natural polymers (chitosan and biocellulose) have sparked interest, especially when it comes to medical uses (wound healing, excipients for drug administration), due to their great biocompatibility and low toxicity [...]